À l'intersection de la presse, de la politique internationale et de la diplomatie : les agences de presse comme instruments transnationaux de diplomatie publique pendant la Guerre Froide - Eduardo Tamayo Belda (Cahiers de Civilisation Espagnole Contemporaine)
The article proposes a reflection on the link between press agencies, image in international politics and diplomacy, particularizing the analysis in the period of the Cold War. The theoretical relationships between these elements are explored, and possible approaches and lines of work are proposed for research that takes these international news agencies as objects of study, from their consideration as corporations that intervene from a transnational logic. This occurs as they are private entities whose activity is carried out in a multiplicity of local scenarios of the global theater, while, at the same time, these agencies may have solid links or shared interests with one or several states, governments, or interest groups.